Performance Metrics in Food and Beverage Investments: A Systematic Reviews of Existing Research - Devi Putri Ananda; Denny Kurnia; Deni Sunaryo (International Conference On Digital Advanced Tourism Management And Technology, 2024)
This literature review explores the dynamics of investment decisions, resilience to economic shocks, and the role of sustainability in the food and beverage sector. Focusing on the impact of capital investment, stock performance, and the application of environmental, social, and governance (ESG) principles, the review shows how the right strategies can enhance corporate value, attract investors, and maintain financial stability in the face of global economic uncertainty. Key findings suggest that investments in fixed assets and human resources have a positive impact on corporate operational performance and competitiveness in international markets. The COVID-19 pandemic is a prime example of the sector’s resilience, prompting companies to rethink their business models and capital expenditures. In addition, foreign direct investment (FDI) in developing countries, especially sustainability-oriented investments, has been shown to positively contribute to local economies. This study contributes by providing strategic guidance for stakeholders to optimize investment decisions in an effort to achieve sustainable growth.